Spatial and Temporal Confinement of the Ionospheric Responses During the St. Patrick's Day Storm of March 2015 - Sk Samin Kader; N. Dashora; K. Niranjan (Space Weather)
Abstract The present study provides a multi‐instrument analysis of the ionospheric response to the effects of the St. Patrick's Day storm of 17–18 March 2015. Simultaneous observations from 85 global positioning system stations and multiple satellites along the past observations from the literature survey are utilized to ascertain the spatio‐temporal confinements between −20°E and 150°E longitudes. The main results include longitudinal differences in the episodic equatorward expansions of the auroral oval which is shown to relate with varying high‐latitude Joule heating and equatorward wind surges at different local times. The zonal movement of equatorial ion density depletions from initially east to west followed by a sluggish westward pattern on the night of 17 March is observed. The zonal movement is found to be better explained by the longitudinally decreasing impact of the disturbance dynamo in the nightside. The enhancements in total electron content during morning on 17 March are observed over mid‐latitudes, which are found to move equatorward in the noon time. These enhancements could be associated with the enhanced O density bulge resulting from the thermospheric expansion during the main phase. A daytime sustained and confined electron density depletion between about 100°E and 170°E is observed on 18 March which is being discussed in detail for the first time. Interestingly, large longitudinal differences are observed in the response of the disturbance dynamo, including no observable effect during morning (−20°E–20°E) but dominant afternoon and westward progression during the day of 18 March.